Evaluasi Implementasi Program Bantuan Operasional Sekolah Dasar (Studi Pada SDN Bulusari Tarokan ) - Ilyas, Taufiq (Jurnal Administrasi Publik, 2013)
Organizing the implementation of a program is not always be balanced with success on the intended target of the main objectives. As well as organizing the implementation of the School Operational Assistance (BOS) at the elementary school (SD). Consistent with the program that has been running more than about eight years from 2005, this program has actually made â€‹â€‹many contributions, particularly in the education service. School Operational Assistance (BOS) to be the main instrument in the teaching and learning activities schools. But even then on the other side dimensions there are real problems in the implementation of the School Operational Assistance (BOS) in elementary school (SD).so what is the vision and mission of the program objectives are not to achieve success. so what is the vision and mission of the program objectives are not to achieve success.Keywords: evaluation, The School Operational Assistance (BOS). Implementasi penyelenggaraan suatu program tidak selamanya selalu diimbangi dengan keberhasilan pada sasaran tujuan utama yang dituju. Seperti halnya implementasi penyelenggaraan program Bantuan Operasional Sekolah (BOS) pada Sekolah Dasar (SD). Sejalan dengan program yang telah berjalan kurang lebih sekitar delapan tahun dari tahun 2005 program ini sebenarnya telah memberikan banyak kontribusi, khususnya pada layanan pendidikan. Bantuan Operasional Sekolah (BOS) menjadi instrument utama dalam terselenggarakannya kegiatan belajar mengajar di sekolah. Namun demikan pada dimensi sisi yang lain masih saja terdapat permasalahan pada implementasi penyelenggaraan program Bantuan Operasional Sekolah (BOS) di Sekolah Dasar (SD), sehingga apa yang menjadi visi misi dari sasaran program tersebut belum mencapai keberhasilan. Kata kunci: evaluasi, Program Bantuan Operasional Sekolah (BOS). Â